INTEGRATED LEARNING OF LAMINAR BOUNDARY LAYER MODELING ON FLAT PLATES USING ANSYS WORKBENCH FOR SHIP MACHINERY MECHANICS AND MECHATRONICS SPECIALISTS) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In engineering disciplines such as ship machinery mechanics and mechatronics, the ability to model and simulate physical phenomena is essential for designing and optimizing complex systems. One of the fundamental topics in fluid mechanics is the laminar boundary layer over flat plates, which plays a crucial role in understanding drag forces, heat transfer, and flow behaviour in naval and mechatronic applications. Accurate modelling of the boundary layer is essential for improving the performance of ship propulsion systems, reducing energy losses, and enhancing the efficiency of fluid-based mechatronic devices. This study presents an integrated learning approach that leverages ANSYS Workbench as a computational tool for teaching and understanding the laminar boundary layer modelling over flat plates. The primary objective is to bridge the gap between theoretical knowledge and practical application by incorporating simulation-based learning into engineering education. By integrating computational fluid dynamics (CFD) simulations with classical theoretical models, students develop a deeper understanding of boundary layer development, velocity profiles, and shear stress distribution. The methodology involves a structured learning process where students first study the fundamental equations governing laminar boundary layers, such as the Blasius solution for incompressible flow over a flat plate. They then proceed with hands-on simulations in ANSYS Fluent, where they define boundary conditions, mesh the computational domain, and analyse numerical results in comparison with analytical solutions. The learning approach encourages active problem-solving and enhances critical thinking skills. The findings demonstrate that simulation-based learning significantly improves students' comprehension of boundary layer theory by visualizing complex flow phenomena. Additionally, the integration of CFD tools fosters practical skills in numerical modelling, which are essential for their future careers in ship machinery mechanics and mechatronics. The proposed method enhances student engagement and provides a systematic framework for applying CFD techniques in engineering education, reinforcing the importance of simulation in modern fluid mechanics.